Social work practice with people with dementia - Scourfield, Peter (London New York Routledge, Taylor & Francis Group, 2023)
Social Work Practice with People with Dementia critically discusses the cultural and discursive contexts in which social work with dementia takes place. Social Work Practice with People with Dementia will be of particular interest to social work students and early career social workers, primarily in a UK context. However, it contains much relevant information about dementia and dementia practice for anyone involved with adult health and social care both in the UK and around the world"--
Includes bibliographical references (pages 165-180) and index.
Keywords: Social work with older people; Social work with people with mental disabilities; Dementia -- Patients -- Services for